Clinical outcomes of early active mobilization following flexor tendon repair using the six-strand technique: short- and long-term evaluations. (March 2015) - Moriya, K.; Yoshizu, T.; Maki, Y.; Tsubokawa, N.; Narisawa, H.; Endo, N.
We evaluated the factors influencing outcomes of flexor tendon repair in 112 fingers using a six-strand suture with the Yoshizu #1 technique and early postoperative active mobilization in 101 consecutive patients. A total of 32 fingers had injuries in Zone I, 78 in Zone II, and two in Zone III. The mean follow-up period was 6 months; 16 patients (19 fingers) participated in long-term follow-up of 2 to 16 years. The total active motion was 230° SD 29°; it correlated negatively with age. The total active motion was 231° SD 28° after repair of the lacerated flexor digitorum superficialis tendon, and was 205° SD 37° after excision of the flexor digitorum superficialis tendon ends ( p  = 0.0093). A total of 19 fingers showed no significant increases in total active motion more than 2 years after surgery. The rupture rate was 5.4% in our patients and related to surgeons' level of expertise. Five out of six ruptured tendons were repaired by inexperienced surgeons. Level of Evidence IV